(untitled) (Humanis, 2026)
Serat Sestradi is a work by Kanjeng Gusti Paku Alam II, containing 21 behavioral guidelines that are regarded as valuable references for moral education in society. Based on the moral values presented in Serat Sestradi, this study aims to classify moral actions through the lenses of Utilitarianism and Deontological ethics. The research employs a qualitative-descriptive approach, utilizing library research, analyzing literature,including books and scholarly articles related to Serat Sestradi and ethical philosophy. The findings reveal that the moral values contained in the 21 guidelines can be classified within the frameworks of both Utilitarian and Deontological ethics.